A novel botybirnavirus with a unique satellite dsRNA causes latent infection in Didymella theifolia isolated from tea plants - Liangchao Ye; Xinyu Shi; Yunqiang He; Jiao Chen; Qingeng Xu; Karim Shafik; Lanning Fu; Yumeng Yin; Ioly Kotta-Loizou; Wenxing Xu (Microbiology Spectrum, 2023)
ABSTRACT The unique, recently discovered fungus Didymella theifolia specifically infects local varieties of tea plant Camellia sinensis in China, and therefore, the characterization of its mycoviruses is important. Three double-stranded (ds) RNAs (1, 2, and 3, with 6,338, 5,910, and 727 bp in size, respectively) were identified in the avirulent D. theifolia strain CJP4-1, which exhibits normal growth and morphology. Characterization of these double-stranded RNAs (dsRNAs) revealed that the two largest elements are the genomic components of a novel botybirnavirus, tentatively named Didymella theifolia botybirnavirus 1 (DtBRV1). Conversely, dsRNA3 shares no detectable similarity with sequences deposited in public databases but has high similarity with the 5′-terminal regions of dsRNAs 1 and 2 and contains a duplicated region encoding a putative small peptide. All three dsRNAs are encapsidated in isometric virions ca. 40 nm in diameter, supporting the notion that dsRNA3 is a DtBRV1 satellite. SDS-polyacrylamide gel electrophoresis in combination with peptide mass fingerprint analysis revealed that the DtBRV1 capsid protein consists of polypeptides encoded by the 5′-terminal regions of both genomic components dsRNA1 and dsRNA2. Vertical transmission of DtBRV1 through conidia is efficient, while its horizontal transmission from CJP4-1 to other strains was not detected. DtBRV1, with or without dsRNA3, has no obvious effects on fungal growth and virulence, as illustrated following transfection of the virulent D. theifolia strain JYC1-6. In summary, DtBRV1 exhibits unique molecular traits and contributes to our understanding of mycovirus diversity. IMPORTANCE A novel botybirnavirus, infecting the tea plant pathogen Didymella theifolia and tentatively named Didymella theifolia botybirnavirus 1 (DtBRV1), together with an additional double-stranded RNA (dsRNA), was characterized. DtBRV1 comprises two dsRNAs (1 and 2) encapsidated in isometric virions, while dsRNA3 is a satellite. The satellite represents a unique specimen since it contains a duplicated region and has high similarity to the two botybirnavirus dsRNAs, supporting the notion that it most likely originated from a deficient genomic component. The biological characteristics of DtBRV1 were further determined. With their unique molecular traits, DtBRV1 and its related dsRNA expand our understanding of virus diversity, taxonomy, and evolution.